Digital Decision Making Tool of Family Planning as a media Innovation Of Family Planning Counceling - Lia Nurcahyani (Jurnal Ilmiah Bidan (JIB), 2020)
One of the strategic issues and quantity control problems of the population that must receive special attention, as stated in the 2015 - 2019 RPJMN is that there is still a high level of unmet need. The cause of unmet need is that the counseling of family planning Information is not optimal which is influenced by the media. In Indonesia, the assistive devices used decision making of family planning (ABPK), but its use is not optimal because ABPK has less practical weaknesses, so mastering the structure and ability of midwives in implementing the steps in the ABPK is still not optimal. This study aims to produce and evaluate Digital ABPK as an innovation of counseling family planning media. This research is qualitative with a case study approach. The research subjects were 6 midwives. This study used the digital ABPK instrument, interview guide, FGD guide and voice recorder. Data analysis through transcription, reduction, making categories,synthesis, and integrating the results of the analysis into descriptive forms. The results showed, digital ABPK had fulfilled the quality of the system, the quality of information and user satisfaction. Midwives will use digital ABPK because it is felt to be easier and more practical than ABPK flipcharts. For further researchers, it is expected to conduct further research on the effectiveness of digital ABPK on knowledge and decision-making of family planning with difference method.